Etika Sosial dalam Pandangan Islam dan Kristen (Studi Kasus Desa Baru, Kecamatan Batang Kuis, Kabupaten Deli Serdang - Irham, Nazmul; Kamaluddin, Kamaluddin; Fitriani, Fitriani (AHKAM, 2023)
This research is entitled Social Ethics in the View of Islam and Christianity (Case Study of Baru Village, Batang Kuis District, Deli Serdang District The purpose of this study is to find out social ethics in Islam and Christianity, to find out how social ethics is in the perspective of Muslim and Christian communities in Baru Village, and to add to the contribution of ideas for scientists in the field of Religious Studies, especially regarding social ethics in Islam and Christianity.In this study, the researcher used a qualitative method that is descriptive by seeking actual and detailed data and information.The research approach used by the researcher was the sociology of religion approach, while the theoretical approach the researcher used was the ethnic approach.The data source of this research are primary and secondary. The data collection technique is by observation, interviews and documentation. The results of this study are; that social ethics is an order that regulates a person's behavior related to association with the environment. This rule is related to the issue of decency, something that is permissible or not to do, as well as about what that person should do. Social ethics in the view of Islamic society says that; Social ethics is an order of individual behavior with society in interacting or socializing which functions to teach and guide people to good behavior and distance themselves from bad behavior. Meanwhile, the Christian view says that social ethics is the order of living together and how a person makes decisions and acts in everyday life, both personally and for others. which means that consciously everything stems from one's conscience, one must feel obliged to do good for the benefit of other human beings besides one's own interests, not personal interests in the sense of being selfish and harming others.